Fetal abnormalities leading to termination of twin pregnancies: the 17-year experience of a single medical center. (1st February 2017) - Melcer, Yaakov; Svirsky, Ran; Vaknin, Zvi; Levinsohn-Tavor, Orna; Feldman, Noa; Maymon, Ron
Abstract: Objective : To assess fetal abnormalities leading to termination of pregnancy (TOP) performed in twin pregnancies. Method : The current study consisted of all women with dichorionic twin pregnancies (study group) who underwent TOP due to fetal abnormalities in our institute from 1999 to 2015. The data were compared to our registry of all parturient women with a singleton pregnancy (control group) that underwent TOP due to fetal anomalies at the same period. Results : There were 2495 cases of TOP because of fetal indications during the study period. Of them, 86 (3.4%) and 2409 (96.6%) were from the study and control group, respectively. Structural anomalies were the leading indication for TOP in twins compared with singleton pregnancies (81.4% versus 50.9%, respectively, p < 0.0001). For twins, the leading indication for TOP was central nervous system (CNS) abnormalities and it was more common compared with singleton pregnancies (26.1% versus 12.2%, respectively, p < 0.0001). This was followed by chromosomal/genetic abnormalities (16.3% versus 40.4%, respectively, p < 0.0001). Conclusions : We found a different distribution for fetal anomalies leading to TOP in twins versus singleton pregnancies. The main indication for TOP in the study group was structural malformations, with a predominance of CNS abnormalities.